Politik (Seksual) atas Tubuh Perempuan: Sejarah Perbudakan Seksual Pada Masa Fasisme Jepang dan Neo-Fasisme Orde Baru di Indonesia, Sebuah Perbandingan - , Anna Mariana, S.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Characters are essential elements in determining someoneâs or some groupâs nature. In the case of a country (regime), the characters are visible from the policies taken by the ruler over various aspects of the societyâs life. In that context, we are permitted to determine a fascist country. Are its characters, authoritarian governmental situation, mono-party political system, dictatorship, racism and militarism. The core character is that the State is supposed to be central in any matter of life. A fascist regime formation once took placed in Indonesa in the time of Japanese colonialism. Citizens mobilization and strict controls over them for the warâs sake is a good example of a real fascist policy. Besides, the regime applied the policies of regulating press, controlling mass organizations, and putting the Stateâs enemies into exile. The inherited fascist characters of the Japanese occupation was reified in the after independence era, that was in the New Order time. The New Order as a fascist regime could be seen in mass mobilization, mono party system, dictatorship, and in its militaristic nature was a real being of a neo-fascist regime. New Order adopted values of facism with modificated in their practise with âPolitical meaningâ and âsmooth orderâfor spread terror over its enemies state. A notable remark for the two fascist regimes eras is the existence of the sexual slavery problems, that left a prolonged traumas for the victims. Sexual slavery of the two regimes was part of their political policies for âsilencingâ the Stateâs enemies. In the time of Japanese occupation, the women turned into sexual slaves were known as Jugun Ianfu, while in the New Order era they were political prisoner women forced to become political power sexual slaves. Understanding the political policies of the two regimes could be an entrance point for explaining why in those two regimes sexual exploitations over women happened. This thesis is to resolve how the characters of a fascist regime provide possibility of violence over women through its political policies. Sexual politics of those regimes eventually dragged their (citizen) women into sexual slavery, annihilated and totally humiliated.